Global experiences of physical distancing, social connectedness and social detachment in COVID-19 pandemic - Rehman, Adeela; Arooj, Hina; Mohamad Diah, Nurazzura; Bakhtawar, Nadia; Kubra, Khadija tul (Psychology and Education, 2021)
The present study aimed to explore the effects of COVID-19 pandemic from global perspective. The study explored physical distancing, social connectedness and social detachment as an outcome of COVID-19 and its impact on individuals. Online survey was conducted from 522 respondents from across the world included, Asia, Europe, Africa and Western region. The participants of the study included wide-ranging age group (18- above 65), both less educated and highly educated, male and female with having single and marries status. The survey was conducted in three weeks’ time periods in the month of April, 2020. The collected data was transformed to SPSS to performed descriptive and inferential statistical analysis. The findings of the study demonstrated significant correlation among physical distancing, social connectedness and social detachment. Simple regression analysis illustrated the significant impact of demographic characteristics on dependent variables. It is concluded that on the one hand, physical distancing was adopted as the only preventive measures against COVID-19, but on the other hand, due to advancement of technology providing multiplicity of online access strengthen social connectedness. However, social detachment is also imitated due to prolonged physical distancing and fragile social relations and interactions. It is recommended that by strengthening social connections, social detachment can reduced and the interval of physical distancing can be utilized more prolifically with the aid of technology